Photonic bandgap characterization of silicon nanorods - Mohd Syuhaimi Ab Rahman; Noor Azie Azura Binti Mohd Arif; Sahbudin Shaari (Universiti Kebangsaan Malaysia, 2010)
Photonic crystals become more attractive in science and technology because of their unique properties. The objective of this research was to study the effect of the size of silicon nanorod in the photoni band structure. This research was carried out by using the RSoft BandSOLVE software. This software uses the Plane Wave Expansion Method (PWEM) to calculate the band structure of photonic crystal. The silicon nanorods used in this work ranged from 0.05 μm to 0.5 μm. The results showed that band structure has a forbidden band for nanorod with size from 0.1 to 0.4 μm.